Health without Borders: INICIB-URP leading Medical Education through Bioengineering and Mechatronic Technologies: Salud sin Fronteras: INICIB-URP liderando la Educación Médica a través de Bioingeniería y Tecnologías Mecatrónicas / 无国界健康：INICIB-URP大学通过生物工程和机电技术引领医学教育 - Vargas, Mariela (2024)
Medical education is at a turning point due to the rapid advances in biomedical technology and robotics in rehabilitation. This editorial examines the importance of integrating these innovations into medical curricula, highlighting statistics on medical education in Latin America and Peru, and discusses the challenges and opportunities for improving the training of future health professionals. In the 21st century, technology is redefining medicine and, consequently, medical education. Biomedical technology and robotics in rehabilitation offer new tools to enhance teaching and clinical practice. In Latin America, including Peru, it is crucial for medical schools to adapt their programs to incorporate these technologies and adequately prepare their students.